Heat transfer in a two-phase closed thermosyphon working in Polar Regions; Thermal Science and Engineering Progress; Vol. 22 - Kuznetsov G. V. Geny Vladimirovich; Ponomarev K. O. Konstantin Olegovich; Feoktistov D. V. Dmitriy Vladimirovich; Orlova E. G. Evgeniya Georgievna; Lyulin Yu. V. Yury Vyacheslavovich; Ouerdane H. Henni (2021, 2021)
Title screen